Challenges Facing People with Disabilities in Accessing Local Government Empowerment Funds in Rombo District Council-Tanzania - Uledi, Saburi Abdallah; Ringo, Cliford J.; Kilugwe, Zuena (Journal of Policy and Leadership, 2025)
This paper examines the challenges facing people with disabilities (PWDs) accessing local government empowerment funds in the Rombo District Council. The study employs social models of Disability (SMD) as a theoretical framework to analyse how societal and institutional factors contribute to the challenges faced by PWDs in accessing empowerment funds provided by the local government. Focus group discussions and semi-structured interviews were administered to 24 participants. Data generated from the study were analysed through content analysis. The results revealed that small funds and disbursement delays, Group formation, disorganisation discrimination and stigmatisation, to mention just a few, were challenges faced by PWDs in accessing the funds. The study concludes that PWDs in the Rombo District Council faced numerous challenges in accessing local government empowerment funds. As highlighted by the SMD, institutional, physical or attitudinal barriers in society respectively create disability by limiting opportunities and full participation of impaired people, including access to funds. The paper recommends the review of institutional frameworks to foster more access to funds and inclusion and change attitudes, traditions and culture to eliminate stigma and segregative behaviour. It will expedite the smooth implementation of the national and global goal of facilitating socio-economic inclusion of the marginalised PWDs among that group.